UMPSA students celebrate 68th National Day, bringing independence spirit to Melbourne - Nur Husna, Azlan (UMPSA, 2025)
MELBOURNE, 31 August 2025 – A total of 15 students from Universiti Malaysia Pahang Al-Sultan Abdullah (UMPSA) who participated in the UMPSA Mobility Expedition Programme@Melbourne celebrated Malaysia’s 68th National Day in Australia with full patriotic spirit.